2017
DOI: 10.1111/aas.12897
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin levels are frequently subtherapeutic in critically ill patients: a prospective observational study

Abstract: BackgroundAppropriate utilization of vancomycin is important to attain therapeutic targets while avoiding clinical failure and the development of antimicrobial resistance. Our aim was to observe the use of vancomycin in an intensive care population, with the main focus on achievement of therapeutic serum concentrations (15–20 mg/l) and to evaluate how this was influenced by dose regimens, use of guidelines and therapeutic drug monitoring.MethodsA prospective observational study was carried out in the intensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
69
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 22 publications
(33 reference statements)
7
69
2
3
Order By: Relevance
“…These variations in pharmacokinetic parameters reflect the underlying illnesses of the patients. In particular, trauma patients have consistently been found to have augmented renal clearance of vancomycin . While data on vancomycin dosing and TDM in critically ill children are sparse, in the neonatal intensive care setting it has been shown that only 25–51% of trough concentrations are within target range with empiric dosing, despite both these studies targeting lower trough concentrations of 5–15 mg/L .…”
Section: Discussionmentioning
confidence: 99%
“…These variations in pharmacokinetic parameters reflect the underlying illnesses of the patients. In particular, trauma patients have consistently been found to have augmented renal clearance of vancomycin . While data on vancomycin dosing and TDM in critically ill children are sparse, in the neonatal intensive care setting it has been shown that only 25–51% of trough concentrations are within target range with empiric dosing, despite both these studies targeting lower trough concentrations of 5–15 mg/L .…”
Section: Discussionmentioning
confidence: 99%
“…The need for clearer guidelines regarding vancomycin dosing and TDM for patient subpopulations has been recently reported …”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Significant challenges in vancomycin use in critically ill patients have been recently identified . There is wide variability in reported practices for antibiotic dosing and monitoring.…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
See 2 more Smart Citations